GAMBARAN KUALITAS HIDUP KESEHATAN MASYARAKAT PADA ERA PANDEMI COVID-19 DI KOTA KENDARI TAHUN 2020 - Apriani Apriani; Hariati Lestari; Harleli Harleli (FKM Universitas Halu Oleo, 2021)
In the COVID-19 pandemic era, the population has experienced several risk factors that can cause adverse physical and mental health problems and affects on quality of the community life. This study aims to describe a life quality of public health in pandemic era at Kendari city in 2020. The method used in this study is a quantitative descriptive study with a cross sectional design. The population in this study were all citizens of Kendari City who were over 17 years old, totaling 211,247 people and the sample of this research is a community of Kendari totaling 384 samples. The sampling technique used in this study is probability sampling, using the proportional stratified random sampling method. Data collection was carried out using a google form-based online questionnaire which were distributed through social media platforms as Facebook and WhatsApp. The instruments used in this study were the the WHOQoL-BREF questionnaire and all question items regarding data on health conditions, employment, family income and marriage. The data obtained were analyzed using univariate analysis. The results of this study indicate that the subjective assessment of the life quality of majority respondents feels that they have a well life quality and based on subjective assessments of the state of health in general that the majority respondents are satisfied with health condition they have. Based on the measurement of aspects of the physical health domain, psychological domain, social relations domain and environmental domain, the majority of Kendari community have a good life quality. The conclusion obtained from this study is a description of the life quality on public health in the era of the COVID-19 pandemic at Kendari city in 2020, that the majority of community get a well health condition and life quality. In addition, community work from home and majority have high income and life quality. Furthermore, majority have a status of being unmarried experiencing in the same thing. By knowing the description of the life quality of public health in the COVID-19 pandemic era at Kendari City, it is hoped that it will be useful in planning and implementing health services, both promotive, preventive, curative, and rehabilitative